EVALUATION OF THE EFFECTIVENESS OF QRIS IN IMPROVING THE SECURITY OF INCLUSIVE FINANCIAL TRANSACTIONS FOR CULINARY UMKM IN PALEMBANG CITY - Rika Fitri Ramayani (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Digital transformation in payment systems is an important factor in encouraging transaction security and financial inclusion for Micro, Small and Medium Enterprises. Quick Response Code Indonesian Standard (QRIS) is a Bank Indonesia innovation that aims to simplify safe and inclusive digital payment transactions. This research aims to evaluate the effectiveness of QRIS in increasing the security of inclusive financial transactions for culinary UMKM in Palembang City. The research uses a quantitative approach with a survey method of 100 culinary UMKM who use QRIS. The data were analyzed using validity, reliability, classical assumption tests, and simple linear regression with the help of SPSS. The research results show that the use of QRIS has a positive and significant effect on increasing the security of financial transactions and encouraging financial inclusion for culinary UMKM. These findings indicate that QRIS is effective as a digital payment instrument that supports an inclusive financial ecosystem at the UMKM level.